HUBUNGAN KESULITAN BELAJAR MATEMATIKA TERHADAP KEMAMPUAN KONEKSI MATEMATIKA PADA SISWA SMK KARTIKA 1 SURABAYA - Elok Hidhayati Hartanti (Universitas PGRI Adi Buana Surabaya, 2016)
This research is motivated by the low ability students' mathematical connections. Mathematical reasoning and connections are two basic mathematical ability that must be mastered middle school students. However, many students have problems and learning difficulties in solving mathematical problems. Through the process of mathematical connections, conceptual thinking and students' horizons will be broader, the students will have the skills to solve problems and make decisions. The problem of this research is